Pemikiran Tarekat Syekh Abdul Qodir Al Jailani Dalam Kitab Al Mukhtasor Fi Ulumiddin - Akhmad Muhaini (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research examines the thoughts of Sheikh Abdul Qodir Al Jailani's order as contained in the book Al Mukhtasor fi Ulumiddin. This book is an important work that describes the principles of Sufism and Islamic religious teachings from the perspective of Sheikh Abdul Qodir. Through in-depth analysis of the text, this research aims to identify the main concepts in his thinking, including the relationship between sharia and nature, as well as the role of the tarekat in achieving closeness to God. The research results show that Sheikh Abdul Qodir's thoughts are not only relevant in a spiritual context, but also make a significant contribution to the development of Islamic thought as a whole.